Calcium influx through muscle nAChR-channels: One route, multiple roles. (15th July 2020) - Grassi, Francesca; Fucile, Sergio
Abstract: Although Ca 2+ influx through muscle nAChR-channels has been described over the past 40 years, its functions remain still poorly understood. In this review we suggest possible roles of Ca 2+ entry at all stages of muscle development, summarizing the evidence present in literature. nAChRs are expressed in myoblasts prior to fusion, and can be activated in the absence of an ACh-releasing nerve terminal, with Ca 2+ influx likely contributing to regulate cell fusion. Upon establishment of nerve-muscle contact, Ca 2+ influx contributes to orchestrate the signaling required for the correct formation of the neuromuscular junction. Finally, in the mature synapse, Ca 2+ entry through postsynaptic nAChR-channels – highly Ca 2+ permeable, in particular in humans – acts on K + and Na + channels to shape endplate excitability. However, when genetic defects cause excessive channel activation, Ca 2+ influx becomes toxic and causes endplate myopathy. Throughout the review, we highlight how Ricardo Miledi has contributed to construct this whole body of knowledge, from the initial description of Ca 2+ permeability of endplate nAChR channels, to the rationale for the treatment of endplate excitotoxic damage under pathological conditions. This article is part of a Special Issue entitled: SI: Honoring Ricardo Miledi - outstanding neuroscientist of XX-XXI centuries Graphical abstract: Unlabelled Image Highlights: Ca 2+ influx through muscle nAChR-channels has been described by Miledi over 40 years ago, but its function is still unclear. In muscle precursor cells, Ca 2+ entry through γ-nAChR contributes to regulate myoblast fusion into multinucleated fibers. At the time of innervation, Ca 2+ influx through γ-nAChR participates in the control of neuromuscular junction formation. ε-nAChR has high Ca 2+ permeability and Ca 2+ entry likely shapes endplate excitability in mature synapses. In some diseases, excessive Ca 2+ accumulation can cause endplate damage.